Mycoplasma bovis: Mechanisms of Resistance and Trends in Antimicrobial Susceptibility - Lysnyansky, Inna; Ayling, Roger D. (Frontiers in Microbiology, 2016)
Mycoplasma bovis is a cell-wall-less bacterium and belongs to the class Mollicutes. It is the most important etiological agent of bovine mycoplasmoses in North America and Europe, causing respiratory disease, mastitis, otitis media, arthritis, and reproductive disease. Clinical disease associated with M. bovis is often chronic, debilitating, and poorly responsive to antimicrobial therapy, resulting in significant economic loss, the full extent of which is difficult to estimate. Until M. bovis vaccines are universally available, sanitary control measures and antimicrobial treatment are the only approaches that can be used in attempts to control M. bovis infections. However, in vitro studies show that many of the current M. bovis isolates circulating in Europe have high minimum inhibitory concentrations (MIC) for many of the commercially available antimicrobials. In this review we summarize the current MIC trends indicating the development of antimicrobial resistance in M. bovis as well as the known molecular mechanisms by which resistance is acquired.